Analysis of quality of life in older adults in the Czech Republic and Brazil – a systematic review - Corazza, Sara Teresinha; Vacková, Jitka; Costa, Damiana Lima (Pontifícia Universidade Católica de São Paulo, 2019)
The objective of this study was to search for original articles that approach the Brazilian and Czech elderly’s quality of life in different dimensions. A systematic review was developed and the searches were carried out in Pub-Med/MEDLINE, LILACS, SciELO and PsycINFO databases. The quests were performed using the English language, over the period ranging from July 2008 through June 2018. Thirty studies, 27 with Brazilian elderly, 2 with Czech elderly and 1 with both populations, were found according to selected inclusion criteria. The results show that the Czech elderly have a lower quality of life perception than the Brazilian ones. When living in rural areas, the latter showed good results for autonomy, psychological and physical factors as well as low consumption of alcohol and tobacco. The different dimensions of quality of life can be improved for the Czech and Brazilian elderly for health education and social purposes.
Keywords: Quality of life; Elderly; Czech Republic; Brazil.